Pemberdayaan Gender, Indeks Pembangunan Manusia, dan Ketahanan Keluarga (Studi Kasus di Daerah Relatif Tertinggal Provinsi Jawa Timur) - Sari, Indah Purnama; Subiyantoro, Heru; Miftah, Zaeni (Jurnal Kajian Stratejik Ketahanan Nasional, 2020)
The Covid 19 pandemic has an impact on the resilience of Indonesian families because from an economic standpoint, many people have lost their jobs and sources of income due to the pandemic. Family resilience is basically the foundation of national resilience, which aims to protect the entire nation and achieve security and prosperity. The important role of women cannot be ignored in realizing family resilience. Women can help increase family income so that community welfare will also increase. This study examines how gender empowerment as a strategy for family resilience can improve welfare (Human Development Index). The research was conducted in 2020 in relatively disadvantaged areas in East Java Province. The population in this study includes 16 districts, all members of the population as the sample. The data used is secondary data from BPS East Java Province. The data were processed using the panel data regression method. The results showed that gender empowerment had a significant effect on increasing the Human Development Index in low growth low income areas in East Java. The government concerned can make gender empowerment a strategy for family resilience in order to improve people's welfare. Keywords: Gender empowerment; Human Development Index; Family Resilience